Embracing plurality through oral language - Bich, N.; Oliver, Rhonda; Rochecouste, J. (TESOL, 2014)
The transmission and dissemination of knowledge in Aboriginal societies mainly occurs orally in a traditional language or in Aboriginal English. However, in schools little place is given to developing equivalent communicative competence in Standard Australian English. Further, the ongoing assessment of reading and writing skills are in direct contrast to the existing oral language experience of Aboriginal students.